Identyfikacja przemieszczeń pionowych obiektów budowlanych zlokalizowanych na terenie miasta Zielona Góra = Identification of vertical displacements of building structures located in the city of Zielona Gora - Mrówczyńska, Maria; Gibowski, Sławomir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this paper is to present the results of surveys and analyses of subsidence conducted on selected buildings in Zielona Gora, located at 1-3 Leopolda Staffa Street and 8 Dekoracyjna Street. Although these buildings are particularly noteworthy from a geotechnical perspective, the topic remains broad, with other significant buildings worthy of further exploration, such as the PZU building located opposite the former Dom Towarowy Centrum at Bohaterow Westerplatte Street, the A-8 building of the University of Zielona Gora, which houses the Institute of Civil Engineering, and the multi-family building at 13 ABCDE Szafrana Street, situated on a former landfill site. The length of this article and the desire to present the topic of vertical displacements in a clear and concise manner were the reasons for limiting the discussion to two cases.
Keywords: przemieszczenia pionowe; definicja geodezyjnego układu odniesienia; vertical displacements; definition of geodetic datum